PENGARUH LIKUIDITAS, LEVERAGE, MANAJEMEN LABA, DAN KOPENSASI RUGI FISKAL TERHADAP AGRESIVITAS PAJAK PERUSAHAAN PADA PERUSAHAAN PERTANIAN DAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - Purwanto, Agus; ', Yusralaini; ', Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the effect of the liquidity, leverage, earnings management, and compensation tax losses against corporate tax aggressivenesss on agriculture and mining companies listed in Indonesia Stock Exchange (BEI) 2011-2013. The sample used in this study is agriculture and mining company listed on the Indonesia stock exchange is based on criteria that have been set. The sampling method used is purposive sampling and testing this hypothesis using multiple linear regression analysis. Proxy calculation of corporate tax aggressiveness in this study using a proxy CETR (Cash Effective Tax Rate) and the results of this study showed that the independent variables are liquidity, leverage, and earnings management significantly influence the partial on corporate tax aggressiveness, but the variable compensation tax losses has no effect the partial on corporate tax aggressiveness, and the results of coefficient of determination (adjusted R2) of 0.537. This suggests that the overall effect of independent variables are Liquidity, Leverage, Earnings Management, and Compensation Tax Losses against Corporate Tax Aggressiveness to 53,7% while the remaining 46,3% is influenced by other variables.Keywords: Corporate Tax Aggressiveness, Liquidity, Leverage, Earnings Management, and Compensation Tax Losses